1987
DOI: 10.1007/bf00696374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of facial fanning on local exercise performance and thermoregulatory responses during hyperthermia

Abstract: To investigate the effects of hyperthermia and facial fanning during hyperthermia on hand-grip exercise performance and thermoregulatory response, we studied eight male subjects, aged 20-53 years. Subjects exercised at 20% of maximal hand-grip strength in the sitting position under three conditions: normothermia (NT), hyperthermia without fanning (HT-nf) or with fanning at 5.5 m X sec-1 wind speed (HT-f). Hyperthermia (0.5 degrees C higher oesophageal temperature than in NT) was induced by leg immersion in wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

1987
1987
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 25 publications
1
8
0
2
Order By: Relevance
“…Similar reduction was seen for RPE legs , although in this case the differences remained statistical significant. These results are in agreement with previous observations, where a positive action of face fanning during hyperthermia on RPE and performance of local muscle contractions was demonstrated (Hirata et al 1987).…”
Section: Fig 3 Graphs Depict Values Forsupporting
confidence: 95%
“…Similar reduction was seen for RPE legs , although in this case the differences remained statistical significant. These results are in agreement with previous observations, where a positive action of face fanning during hyperthermia on RPE and performance of local muscle contractions was demonstrated (Hirata et al 1987).…”
Section: Fig 3 Graphs Depict Values Forsupporting
confidence: 95%
“…Olshewski and Bru篓ck (1988) have demonstrated that endurance time on a cycle ergometer was increased by 12% when the subjects were precooled by being exposed to 5-10掳C for 30 min just before the beginning of exercise. Hirata et al (1987) have found that handgrip exercise performance was markedly decreased by hyperthermia which was induced by hot water bath immersion of both legs. Therefore, the skin pressure caused by sportswear worn in a warm environment could produce quicker increase of core temperature, resulting in faster fatigue.…”
Section: Discussionmentioning
confidence: 98%
“…A large number of studies have investigated the influences of human face or head cooling on thermal comfort [3], sweat rate [35], work load [18], and heart rate [10,32] when hyperthermic. The majority of them demonstrate that artificial head cooling in hyperthermic subjects reduces brain temperature, as inferred from the reduction of T ty .…”
Section: Discussionmentioning
confidence: 99%